Analysis of dietary behaviour in physically active persons’ cohort - Plavina Liana; Umbraško Silvija; Asare Lāsma; Lindemanis Gints (SHS Web of Conferences, 2024)
Physical and psychological load need dietary support of energy by balanced diet. Dietary intake influences physical fitness and training performance outcomes of participants. The purpose of the study was to evaluate the nutrition behaviour from physically active persons and impact of nutrition knowledge on their nutritional behaviour. Respondents were at the age of 22-35 years. Respondents of study group got general knowledge about balanced diet in the nutritional education course. Respondents of the study group fulfilled the standardized questionnaire ‘Diet 3-day menu diary’ and standardized survey ‘Physical activity during the current life period before and after nutritional education course. That allows researchers to evaluate the balance between daily intake for energy recovery and daily physical activity as energy expenditure. The study was carried out according to ethical rules for obtaining and processing data. All obtained data was anonymised. The results of the study could be used to develop appropriate diet planning during the pre-training period before planning physical exercises with high physical and psycho-emotional load to improve exercise performance.